(untitled) (Journal of the College of Education for Women, 2019)
This research is about the resources and the way of al-Waqidi in hisresearching of al-sira of the Prophet. And what happened in the first of Islam.This research is about the documents which al-Waqidi had it. Some of it,which he had visited, was the places, especially the periods which the events had tookplace in. He was asking those whom were contemporary to the happenings, from thesons of al-Sahaba and al-Tabi’een.Also this research is lightening on the new studies that gave this historian agood respect during his work, in which he could gave the reality about his authorship.The research is trying to draw real way of al-Waqidi and what were reported by him,especially the documents, and what he had seen. This will met edited especially thereal account of his book “Fituh al-Shaam”, if we don’t do it.